A review on the processing technique, physicochemical, and bioactive properties of marine collagen - Shaik, Mannur Ismail; Abdul Rahman, Siti Hajar; Yusri, Anis Syafiqah; Ismail Fitry, Mohammad Rashedi; Kumar, Nune Satya Sampath; Mhd Sarbon, Norizah (John Wiley and Sons Inc, 2024)
Collagens are conventionally derived from bovine and porcine sources. However, these sources were commonly associated with infectious diseases such as bovine spongiform encephalopathy, foot and mouth disease, autoimmune and allergic reactions, and religious constraints. The significant amount of collagen available in marine species, especially fish skins, scales, fins, and bones, shows that marine species can be a potential alternative source to mammalian collagen. Therefore, this review aims to give a clearer outlook on the processing techniques of marine collagen and its physicochemical and bioactive properties as a potential alternative to mammalian collagen. The two most suitable extraction methods for marine collagen are pepsin-soluble extraction and ultrasound-assisted extraction. Additionally, marine collagen’s physicochemical and bioactive properties, such as antioxidants, wound healing, tissue engineering, and cosmetic biomaterial have been thoroughly discussed in this review.